"Surface-line-point"—analysis of the development of artificial intelligence in the Yangtze River Delta. (November 2020) - Liang, Yao; Hu, Yuewei
Abstract: Artificial intelligence technology is booming all over the world, profoundly affecting the social and economic development model and people's lifestyle. The Yangtze River Delta urban agglomeration, which has a very high strategic position in the country's modernization and comprehensive opening up, is an important support for China's participation in international competition and a gathering place for China's cutting-edge technology. The Yangtze River Delta has become the leader of my country's artificial intelligence technology and industry by virtue of its advantageous geographical location, active economic development, high-density talent pool and years of development and accumulation in the field of artificial intelligence. From "surface-line-point", the article analyzes the advantages and disadvantages of the rapid development of artificial intelligence in the Yangtze River Delta; combines the education industry to analyze the integration of artificial intelligence and education and possible bottlenecks; conforms to the trend of the times and shows the new Internet celebrities of programming world—python.